10(6+2x)=-2(8x+6)

Simple and best practice solution for 10(6+2x)=-2(8x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(6+2x)=-2(8x+6) equation:


10(6+2x)=-2(8x+6)

We simplify the equation to the form, which is simple to understand
10(6+2x)=-2(8x+6)

Reorder the terms in parentheses
+(+60+20x)=-2*(8x+6)

Remove unnecessary parentheses
+60+20x=-2+*(+8x+6+)

Reorder the terms in parentheses
+60+20x=+(-16x-12)

Remove unnecessary parentheses
+60+20x=-16x-12

We move all terms containing x to the left and all other terms to the right.
+20x+16x=-12-60

We simplify left and right side of the equation.
+36x=-72

We divide both sides of the equation by 36 to get x.
x=-2

See similar equations:

| (-4x^2)+(5y)-(-6x^2)-(7y)=x | | Hg(x)=3.08(138)sqrt+18.97 | | 9+-4=x | | f(-3)=3(-3)-15 | | ln(x^2+7x-31)=0 | | 6x^2-16x-360=0 | | 9(y+9)=6+8y | | 10x-5=0 | | 15-n=n+5 | | 2(p-1)=7p+3-4p | | 15-n=5+n | | 5X+2=3X-(8x+2) | | -6+(-4)=x | | 15+n=5+n | | 10+n=n+5 | | 3r+3=6r-1 | | -3+8h=-5 | | -0.002x^2+0.5x-10=0 | | 7p-14=3(p-8)-6(3-3p) | | 3x+2=2-3x | | 6d+7=39 | | 9/7= | | X^3-100x^2-1250=0 | | 45*n=400 | | 4(z-2)=2(z+3) | | 55*t=400 | | 40+1.75c=3.75c | | 82=3(-3x+3)+1 | | -10k+1=40-7k | | 9/20= | | (x+7)x^2-(x+(-2))(x+(-1))=0 | | .07p+4.6=7.3-0.2p |

Equations solver categories